Kajian Filsafat Hukum terhadap Kedudukan Hak Waris Anak Yang Dihukumi Tiada Oleh Orangtuanya di Kabupaten Gowa - Khiar. M, Mafaati Hul; Bakry, Muammar (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This research discusses the practice of inheritance law against children who are punished for being absent by their parents (Dipattompo' Butta) in the Islamic community in Gowa Regency in 2019-2023. Through initial observations, the authors found several cases of inheritance to children whose parents had punished them as dead where the parents did not pay attention and visited their children again where this could cause disputes so the authors felt the need to do research in this regard. This study uses descriptive qualitative field research methods with an empirical legal approach, the data source is through interviews with parents as inheritance owners, children as heirs, the community, and religious leaders in Gowa Regency. The results of the study show that in the practice of inheritance to children whose parents do not punish them (Dipattompo' Butta) in the Islamic community in Gowa Regency, when viewed from the point of view of Islamic Law Philosophy, the dominant use of customary inheritance law or in accordance with the customs of the community both from the distribution of inheritance and the settlement of inheritance disputes. There needs to be socialization of inheritance law, strengthening the legal status of inherited assets and heirs who are entitled, so that there is justice for the heir. By conducting this research, it is hoped that the local government will make it more efficient in providing socialization of inheritance law to the community, especially to children who are punished for being absent by their parents and strengthening legal legality of inheritance, especially regarding certificates of inherited land and heirs who are entitled, so that inheritance disputes due to people's lack of understanding of the law can be minimized.